Tinjauan Yuridis terhadap Pelaksanaan Informed Consent dalam Perjanjian Terapeutik - Kastania Lintang (Jurnal Hukum Lex Generalis, 2021)
Doctors as health care providers who work in health care facilities will provide health services to patients as recipients of health services. Doctor-patient relationships are based on trust relationships and give rise to therapeutic agreements. The agreement is listed in Article 1313 of the Civil Code, as well as the terms of the validity of an agreement listed in Article 1320 of the Civil Code. The legal subjects of therapeutic agreements are patient and doctor. However, the legal object is health care. Before carrying out therapeutic agreements must be preceded by Informed Consent made by the doctor for the patient. Informed Consent is listed in the Permenkes RI No. 290/MENKES/PER/III/2008 concerning Approval of Medical Action. Filling the form must be done appropriately so it will not cause problems in the future.